Proceedings of SPE International Symposium on Oilfield Chemistry 1993
DOI: 10.2523/25203-ms
|View full text |Cite
|
Sign up to set email alerts
|

Ion Exchange Between Hydrogen and Homoionic Brines Related to Permeability Reduction

Abstract: Formation damage due to clay migration may be observed when the injected brine replaces the connate water during operations such as waterflooding, chemical flooding including alkaline, surfactant and polymer processes. This work deals with the effects of physico-chemical changes induced by brine replacement on the permeability behavior of consolidated argillaceous sandstones. The experimental investigation is made up of:-core flow experiments in clayey sandstones. Effluent pH and ionic concentration are measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…RezaeiDoust et al (2011) reported modest increases in oil recovery when injecting higher salinity NaCl brine into a core containing crude oil and CaCl2 brine, and argued that this reflected the differing affinities of Na + and Ca 2+ cations toward clay mineral surfaces, consistent with the model predictions. Ion exchange leading to pH increase has been observed and modelled in other studies relating to formation damage, although these studies considered only monovalent ions in single phase flow (e.g Vaidya and Fogler, 1990;Souto and Bazin, 1993…”
mentioning
confidence: 99%
“…RezaeiDoust et al (2011) reported modest increases in oil recovery when injecting higher salinity NaCl brine into a core containing crude oil and CaCl2 brine, and argued that this reflected the differing affinities of Na + and Ca 2+ cations toward clay mineral surfaces, consistent with the model predictions. Ion exchange leading to pH increase has been observed and modelled in other studies relating to formation damage, although these studies considered only monovalent ions in single phase flow (e.g Vaidya and Fogler, 1990;Souto and Bazin, 1993…”
mentioning
confidence: 99%
“…Jones 1 reported the capabilities of small proportions of divalent cations, such as calcium and magnesium, for controlling clay blocking. Souto et al 4 dealed with the effects physico-chemical changes induced by brine replacement on the permeability behaviour of consolidated argillaceous sandstones. Clays having sufficient adsorbed calcium and magnesium resisted dispersion by water and consequent blocking of permeability.…”
Section: Effect Of Brine Compositionmentioning
confidence: 99%
“…In Figure 6, from the concentration profiles of NaOH at the effluent, 40 000 ppm brine + 0.6 % NaOH concentration curve shows that the front of the solution was stable. Figures 12 and 13 show the changes in permeability reduction with injected volume of NaOH and NaSiO 4 . The distilled water + 0.4 % NaOH alkaline solution gave less oil recovery while the others gave incremental oil recovery when compared with the base flood.…”
Section: Alkali Flood Experimentsmentioning
confidence: 99%
“…Alkali, polymer and surfactant species adsorptions are Langmuir-like [17,18]. More sophisticated is the case of the surfactant, where the Langmuir plateau is a product function of the water salinity (say chloride and sodium ions concentrations) and pH (say hydroxide ions concentration), in order to take into account the alkali effect on limiting the surfactant adsorption:…”
Section: Saripmentioning
confidence: 99%